ANALISIS LABA PADA PT. EIRENE HUMINDO PERKASA SAMARINDA SETELAH PERUBAHAN SISTEM SAMPLER HARIAN MENJADI TENAGA BORONGAN - Lutfiah, Siti Mariatul (EKONOMIA, 2015)
This study aims at finding out the performance of PT. Eirene Humindo Perkasa Samarinda management in its income statement and the significance in the changes of profit after the change in the payment system for samplers from time work to piecework system in the period of 2012â€“2013.The research question of this study was: â€œIs there any significant changes of profit in PT. Eirene Humindo Perkasa Samarinda after the application of piecework payment system to the samplers?â€ The theoretical bases used in this study are financial management, financial statement, income statement, financial ratio analysis, ratio of income statement, parametric t-test, independent sample t-test and outsourcing. Hypothesis of the study was: â€œThere is a significant change in the profit of PT Eirene Humindo Perkasa Samarinda after the application of piecework payment system.â€Analysis and hypothesis testing instrument used in this study was the ratio of the income statement, including Gross Profit Margin, Operating Profit Margin and Net Profit Margin, and Independent sample t-test.The analysis showed that the level of the income statement ratio of PT Eirene Humindo Perkasa Samarinda in 2012-2013 was good, because in the two-year period, the rate of Gross Profit Margin, Operating Profit Margin and Net Profit Margin increased. On average, the Gross Profit Margin level was 72.173%, Operating Profit Margin 38.710%, and net profit margin 26.683%. The level of significance of the change in profit after the application of piecework payment system by using Independent sample t-test was significant, i.e., 2.998 (t-value > t-table, 2.998 > 2.074 and 2.998 > 2.819).Those findings show that there is a significant change in the profit of PT. Eirene Humindo Perkasa Samarinda after the application of piecework payment system. Thus, the hypothesis of the study is accepted